2021
DOI: 10.3390/polym13162595
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline: Doping and Functionalization with Single Walled Carbon Nanotubes for Photovoltaic and Photocatalytic Application

Abstract: Polyaniline (PANI) was chemically doped and functionalized with single walled carbon nanotubes (SWCNTs). Various characterization methods were employed to study the structure and optical properties of PANI/SWCNTs nanocomposite, such as Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), scanning electron microscopy (SEM), optical absorption, and stationary photoluminescence. Additionally, a theoretical study using density functional theory calculations was also carried out. It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…Using Equation (1), the V oc is estimated at nearly 1.25 V, and using the Scharber diagram, PCE is estimated at 4–5% ( Figure 16 (2)). This is in good accordance with our previous PL results showing both the quenching effect and the total absence of luminescence in the visible region [ 116 ].…”
Section: Pani/swcnt Nanocompositessupporting
confidence: 93%
See 1 more Smart Citation
“…Using Equation (1), the V oc is estimated at nearly 1.25 V, and using the Scharber diagram, PCE is estimated at 4–5% ( Figure 16 (2)). This is in good accordance with our previous PL results showing both the quenching effect and the total absence of luminescence in the visible region [ 116 ].…”
Section: Pani/swcnt Nanocompositessupporting
confidence: 93%
“…Following the same procedure, PANI, known by a number of oxidation degrees, is also functionalized with CNTs. The starting material, the emeraldine base (PANIEB purity 99.99%; macromolecular mass Mn > 15,000), is first doped with sulfonic acid and then functionalized with SWCNTs in the dimethylformamide (DMF) solvent [ 116 ]. The sulfonic acid doping procedure used in this case is described by MacDiarmid et al [ 117 ].…”
Section: Pani/swcnt Nanocompositesmentioning
confidence: 99%
“…The optical band gap of pure PANI film was calculated to be 2.6 eV. The bandgap of PANI is in the range of 2.6 eV–3.75 eV, according to the literatures [39,42,101–102] . The direct bandgap calculated for all the samples using the Tauc relation is given in Table 4.…”
Section: Resultsmentioning
confidence: 99%
“…The bandgap of PANI is in the range of 2.6 eV-3.75 eV, according to the literatures. [39,42,[101][102] The direct bandgap calculated for all the samples using the Tauc relation is given in Table 4. It is observed that as the doping concentration of MWCNT increases, the bandgap decreases.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…Among these materials, polyaniline (PANI) and poly(N-vinyl carbazole) PVK are largely studied for their excellent properties [4,5,6], especially the electron excess related to the nitrogen atom present in both materials. In our previous works [6,7,8,9], we demonstrated that these materials could be functionalized with lower concentration single-walled carbon nanotubes (SWCNTs). For both PANI and PVK, the exchange process with SWCNTs is governed by a covalent functionalization and leads to a charge transfer from the polymeric matrix to the SWCNTs.…”
Section: Introductionmentioning
confidence: 99%